Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Materi Suara Hati dengan Metode Problem Based Learning (PBL) Berbantu Video Fase E Kelas X SMA PGRI Purwoharjo-Banyuwangi - Fransiska Niken Trihartanti; YL Sukestiyarno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning in Class X, Phase E, at SMA PGRI Purwoharjo-Banyuwangi in the subject of Catholic Religious Education and Character Development with the topic "Conscience" has shown limitations in the variety of teaching methods. This has impacted the low learning outcomes of students and the failure to achieve the target in the competent and developing categories as expected. The average learning outcomes before the intervention showed that only 30% of students achieved scores above the Minimum Mastery Criteria (KKM), while the rest were in the non-competent category. This study aims to improve student learning outcomes through the implementation of the Problem-Based Learning (PBL) method, supported by video media. The PBL method was chosen because it encourages students to actively think critically, identify problems, and find relevant solutions independently. The use of video as a supporting medium aims to visualize abstract concepts, thereby strengthening students' understanding of the subject matter.This classroom action research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects consisted of 9 Catholic students, and the material discussed included the concept of conscience according to Catholic Church teachings, the steps for making sound decisions based on conscience, and the application of moral principles in everyday life. The instruments used in this study included learning outcome tests, observation sheets, and interviews to measure student engagement and understanding.The success indicators of this study include the students' ability to formulate moral problems related to conscience, ask critical questions, answer questions based on analysis from various sources, and their ability to make ethical decisions in line with Catholic moral principles. In Cycle I, the percentage of students who reached competence was only 68%, with many students still struggling to understand the application of conscience in daily life. However, in Cycle II, the results showed a significant improvement, with 85% of students achieving competence and progressing as expected. This improvement was also evident from the observation of student activities in class, where active participation and critical thinking skills improved. In addition to cognitive observations, affective data comparisons from Cycle I and Cycle II showed an increase in the critical thinking dimension of the Pancasila Student Profile (P3) character, rising from 69.44% to 87.88% during the learning process using the PBL method. Thus, learning with the Problem-Based Learning (PBL) method, supported by E-LKPD on the Pancasila Student Profile (P3) character in the dimensions of Creative and Critical Thinking, has had a positive impact by enhancing the Critical Thinking dimension of the Pancasila Student Profile (P3) in students. This study proves that the application of the PBL method, supported by video media, not only improves student learning outcomes but also facilitates the development of critical thinking skills and problem-solving relevant to everyday life. Furthermore, students demonstrated a better understanding of how conscience plays a role in moral decision-making. The suggestions based on the results of this study emphasize the need for more interactive and contextual learning methods, especially in the subject of Catholic Religious Education and Character Development. The use of visual media, such as video, is recommended as an effective tool to clarify abstract concepts and motivate students to participate more actively in the learning process. Overall, the focus on the critical thinking dimension using the PBL method with video assistance has proven effective in improving critical thinking and academic performance in the subject of Catholic Religious Education in Class X at SMA PGRI Purwoharjo